Mengukur Kinerja AI : Perbandingan Kepuasan Pengguna ChatGPT dan Google Gemini dalam Era Digital - Buana, Pratama Angga; Abriansah, Fausta Rizky; Kurniawan, Nanda Dwi; Ferdian, Praditya Rendi; Ma’arif, Daffa Nurin Nabil; Firdaus, Azmi Maulana (Jurnal Ilmiah SINUS, 2025)
This study aims to analyze user satisfaction with the artificial intelligence applications ChatGPT and Google Gemini using the End-User Computing Satisfaction (EUCS) method. This method evaluates five key dimensions: content, accuracy, format, ease of use, and timeliness. Data were collected from 78 respondents with diverse backgrounds using a Likert-based questionnaire. The results show that both applications fall into the "Satisfied" category, with average scores across all variables exceeding 3.70. ChatGPT scored highest on ease of use (3.93), while Google Gemini excelled in format (3.89). However, the accuracy variable received the lowest scores for both applications, at 3.57 for ChatGPT and 3.73 for Google Gemini. These findings highlight the need for improvements in information accuracy. This study is essential for providing practical insights for developers to enhance the quality of AI applications, making them more responsive to user needs.